Adaptive governance to typhoon disasters for coastal sustainability: A case study in Guangdong, China. Issue 54 (December 2015) - Lei, Yongdeng; Liu, Chengcheng; Zhang, Linbo; Wan, Jinhong; Li, Daiqing; Yue, Qi; Guo, Yang
Highlights: Adaptive governance is essential for disaster risk management in a changing climate. A sound adaptation needs multi-stakeholder participation and multi-scale coordination. Non-structural measures and resilience building is cost-effective for sustainability. Abstract: Globally, more people and assets are concentrated on the limited coastal plains where they are exposed to frequent disasters, such as typhoons, rainstorms and floods that often result in tremendous casualties and economic losses. Based on the causal analysis of the historical typhoon cases in the Guangdong Province of China, this study indicates that structural measures alone are not sufficient to resist and offset the impacts caused by typhoon disasters. Additionally, structural measures are unsustainable due to their high investment and low security. Adaptive governance, which uses non-structural measures and resilience building, is a feasible and cost-effective strategy for responding to the cascading effects of typhoon disasters. Multi-stakeholder participation and vertical–horizontal coordination are essential for providing adaptive governance to typhoon disasters. A risk-sharing model was put forward by bringing together the government, insurance companies and victims. Furthermore, a favorable atmosphere for public participation in disaster risk reduction can be fostered and should be a long-term adaptation strategy. The views and frameworks of adaptive governance provide policy makers with insights on coastal disaster risk management within the broader context of climate change.